Case-control study in young people living in fluoridated and non-fluoridated regions (Research, Society and Development, 2021)
The objective of this study was to verify the prevalence and severity of dental caries in 12-year-olds from a municipality that regularly performs fluoridation of public water supply, since 1972, comparing oral health conditions among young people born and unborn at the site. This is a case-control study, carried out on 164 12-year-old schoolchildren enrolled in public schools in a municipality that continuously performs fluoridation of the water in the public water supply system. The control group was composed of young people with DMFT=0 (n=82) and the case group was composed of young people with DMFT>0 (n=82). The fact that he was not always born and lived in the municipality was considered the exposure factor. The evaluation of the dental condition was performed using the DMFT index. It was found that the average DMFT index of 164 students was 1.00±1.24. There was a statistically significant association (p=0.001) between dental caries experience and the exposure factor, with odds ratio=3.0134 (95% CI=1.5944 - 5.6595). The means of the DMFT index (unexposed=0.44±0.67; exposed=1.31±1.32), of the decayed teeth component (unexposed=0.12±0.34; exposed=0.49±0.89) and the filled teeth component (unexposed=0.40±0.73; exposed=0.83±1.05) were significantly lower (p